2016
DOI: 10.1007/s10344-016-1040-y
|View full text |Cite
|
Sign up to set email alerts
|

First live offspring of Amazonian brown brocket deer (Mazama nemorivaga) born by artificial insemination

Abstract: The Amazonian brown brocket deer (Mazama nemorivaga) is an endemic species of the Amazon rainforest region, which has suffered constant threats due to hunting and increasing deforestation. Artificial insemination (AI), combined with genomic banks, is considered an important tool for maintaining conservation programs of endangered species; however, the number of live offspring born from AI in nondomesticated cervids is extremely low. Thus, studies designed to develop, adapt, or enhance AI techniques are of fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In deer, an epidural block is problematic and stressful during the post-procedure period, when the animal may recover from sedation without return pelvic limb movement. Thus, in addition to the chemical restraint protocol traditionally used by NUPECCE 17 , the association of a slow infusion of fentanyl citrate (2.5 µg/kg) was performed to mitigate the signs of discomfort during the intraoperative period. After the procedure, the females received dipyrone/hyoscine (0.4mg/kg) 24 to prevent post-procedural pain sensitivity, as done in sheep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In deer, an epidural block is problematic and stressful during the post-procedure period, when the animal may recover from sedation without return pelvic limb movement. Thus, in addition to the chemical restraint protocol traditionally used by NUPECCE 17 , the association of a slow infusion of fentanyl citrate (2.5 µg/kg) was performed to mitigate the signs of discomfort during the intraoperative period. After the procedure, the females received dipyrone/hyoscine (0.4mg/kg) 24 to prevent post-procedural pain sensitivity, as done in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The TCAI techniques of the present study have great potential for use in other deer species in different conservation centers (Zoos, Breeding Institutions, and Scienti c Breeding Institutions) due to their greater practicality compared to other techniques, such as laparoscopy or laparotomy. Thus, they appear as a practical and replicable alternative for the genetic management of a great variety of captive populations, which are necessary genetic resources for the conservation of free-living populations and so the species 3,17 . Moreover, the chosen TCAI techniques showed satisfactory results in brow brocket females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females in estrus manifest an increase in the rate of urination, decreased reactivity to the presence of the handlers, lordosis response to the handlers, which is often accompanied by a rapid wagging of the tail (Figure 3A), vulvar hyperemia, and abundant mucoid translucent discharge. Studies have shown the occurrence of such signs in B. dichotomus [89], M. americana [95], and M. nemorivaga [96].…”
Section: Control Of the Estrous Cycle And Artificial Inseminationmentioning
confidence: 99%
“…However, the biggest obstacle regarding deer TCAI is the anatomy of the cervix, which, similar to sheep, has a tortuous cervical canal with reduced dimensions 6 , 18 . Despite this, there is one successful report for the cervical canal transposition and semen deposition in the uterine lumen of a Passalites nemorivagus (formerly Mazama nemorivaga ) 19 female, giving rise to a healthy offspring 20 . Unfortunately, despite this successful report, there have been no reports of other attempts on Neotropical deer.…”
Section: Introductionmentioning
confidence: 99%